Association between Life’s Crucial 9 and bowel health among US adults: a cross-sectional analysis of NHANES 2005–2010 with external validation - Wang, Xueman; Dong, Jian; Lian, Bo; Jiang, Xintong (Frontiers in Medicine, 2025)
BackgroundAbnormal bowel health, including constipation and diarrhea, is common in the general population. The American Heart Association recently introduced Life’s Essential 8 (LE8) as a framework for assessing cardiovascular health (CVH). Building on this, Life’s Crucial 9 (LC9) was developed by adding psychological health as a ninth component, providing a more holistic measure of overall health. Our objective was to investigate whether LC9 is linked to bowel health. To our knowledge, this is the first study to examine the association between LC9 and bowel health outcomes using nationally representative data, with validation in an independent hospital-based cohort.MethodsThis cross-sectional analysis included 12,817 adults from Nutrition Examination Survey (NHANES) 2005–2010, and validation was conducted in an external hospital-based cohort of 991 patients. The primary exposure was the LC9 score, and the primary outcomes were constipation and diarrhea. The primary analysis used weighted multivariable logistic regression to assess the associations of LC9 scores with bowel outcomes. Restricted cubic splines (RCS) were applied to evaluate potential non-linear relationships. Sensitivity and stratified analyses were performed to test the stability of the results. Internal validation was conducted within the U.S. NHANES cohort, and external validation was performed using a hospital-based cohort from our center to confirm robustness and generalizability.ResultsAfter adjusting for potential confounders, higher LC9 scores were significantly associated with a lower risk of both constipation [adjusted odds ratio (AOR) = 0.90, p = 0.001] and diarrhea (AOR = 0.82, p < 0.001). Compared to participants in the lowest tertile, those in the highest LC9 tertile showed a reduced risk of constipation (AOR = 0.70, p < 0.001) and diarrhea (AOR = 0.54, p < 0.001). RCS analysis demonstrated a linear dose–response relationship between LC9 and bowel health outcomes. Stratified analyses confirmed consistent associations across most subgroups, with no significant interactions except for race in the LC9-diarrhea relationship. Sensitivity analyses using unweighted logistic models yielded similar results. Validation analyses confirmed consistent performance, with good discrimination, calibration, and net clinical benefit across cohorts.ConclusionA negative linear association was found between LC9 and both constipation and diarrhea in US adults. Future longitudinal cohort studies are needed to assess the association between LC9 and bowel health.